Հայ աստուածաբանական մտքի դպրոց - Վազրիկ Բազիլ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Сегодня в Армянской Церкви существует теологическая филология, но нет богословского мышления. Однако подобное мышление необходимо для вечного процветания и развития Церкви. Школа армянской богословской мысли основана на предании, явлениях и языке. В свете предания богословие истолковывает явления на армянском языке и трактуя, истолковывает предание. Эта троица – предание, явление и язык, соответствует троице «Бог, мир и человек». Основой предания является откровение Слова, а явление – сотворенный мир, язык – человек. Армянская школа богословской мысли занимается этими тремя вопросами. Это важно и для так называемого «благоустройства», которое в традиции Армянской Церкви называется «обновлением». Это слово более уместно, потому что не только человек благоустраивает Церковь, но Бог есть основа обновления Церкви․ Today the Armenian Church has theological philology, but not theological thinking. Such thinking, however, is necessary for the Church to remain evergreen and everlasting. The school of Armenian theological thought is based on the tradition, phenomena and language. In the light of the tradition, theology interprets the phenomena in the Armenian language, and it interprets the tradition by deciphering the phenomena in the Armenian language as a whole. This triad of tradition, phenomenon and language corresponds to the triad of God, world and man. The basis of the tradition is the revelation of the Word, the phenomenon corresponds to the created world, and the language corresponds to man. The Armenian School of Theological Thought deals with the relations of these three. This is also important for the so-called “reformation”, which is named as “renewal” by the tradition of the Armenian Church. This word is more appropriate, because it is not only man that reforms the Church, but God is the basis of the Church renewal.
Keywords: Կրոնագիտություն; Փիլիսոփայություն